2004
DOI: 10.1136/bmj.329.7480.1421
|View full text |Cite
|
Sign up to set email alerts
|

Effect of democracy on health: ecological study

Abstract: Can political regimes be singled out as a factor affecting health? Rating countries by the extent of their freedom is a useful proxy for measuring the effects of democracy on health related variables Although the influence of democracy in preventing famines has been reported, 1 there have been no empirical studies on the relation between the extent of freedom allowed by political regimes and the effect on a nation's health. We explored the effect of democracy on life expectancy and maternal and infant mortalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
149
0
8

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 237 publications
(164 citation statements)
references
References 9 publications
7
149
0
8
Order By: Relevance
“…This may be because there were very few (eleven) low-income countries with high polity ratings. Other researchers have found that higher levels of democracy were associated with lower child mortality rates across countries (Franco et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…This may be because there were very few (eleven) low-income countries with high polity ratings. Other researchers have found that higher levels of democracy were associated with lower child mortality rates across countries (Franco et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Otra de las variables explicativas consideradas en este trabajo, fue el índice de democracia, medida por la organización independiente sin ánimo de lucro promotora de la democracia "Freedom House", organismo que publica un ranking de libertad sobre la base de informantes claves, para la mayoría de los países, clasificándolos como libres, parcialmente libres o no libres, categorización que puede ser usada como un proxi para explorar los efectos de la democracia sobre la salud 22,23 . Este índice considera las características de derechos políticos (reglas electorales; partidos políticos; grupos de oposición al gobierno; participación de grupos minoritarios en el gobierno) y libertades civiles (libertad de expresión, agremiación, asociación, religión, educación; marco legislativo; libertad de actividad económica; igualdad de oportunidad).…”
Section: Métodosunclassified
“…La democracia sólo existe cuando hay: 1) libertades políticas (prensa, reunión y demás), 2) oportunidades sociales (educación, servicios sanitarios), 3) garantías de transparencia (contra la corrupción), 4) facilidades económicas (comercio) y 5) seguridad protectora (paro, pensiones) 9 . En este sentido, la democracia ayuda a promover salud, a incrementar la salud de las poblaciones, incluso si se corrige por riqueza y educación 11 . La democracia logra su efecto sobre la salud a través de unas reglas de juego transparentes y lógicas.…”
Section: Las Instituciones Como Incentivosunclassified